2005
DOI: 10.1371/journal.pgen.0020223.eor
|View full text |Cite
|
Sign up to set email alerts
|

A High-Resolution Map of Synteny Disruptions in Gibbon and Human Genomes

Abstract: Gibbons are part of the same superfamily (Hominoidea) as humans and great apes, but their karyotype has diverged faster from the common hominoid ancestor. At least 24 major chromosome rearrangements are required to convert the presumed ancestral karyotype of gibbons into that of the hominoid ancestor. Up to 28 additional rearrangements distinguish the various living species from the common gibbon ancestor. Using the northern white-cheeked gibbon (2n ¼ 52) (Nomascus leucogenys leucogenys) as a model, we created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Gibbons are known to have a rapid rate of chromosomal evolution among the hominoids, mainly involving large-scale rearrangements and rapid karyotypic divergence (Muller et al 2003;Carbone et al 2006;Roberto et al 2007). In contrast to human and great ape segmental duplications, where ;70% of all largescale evolutionary rearrangements map to regions of segmental duplication (Kehrer-Sawatzki and Cooper 2008), initial studies of the gibbon reported that only 46% of gibbon breakpoints mapped to sites of segmental duplication in the human lineage (Carbone et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Gibbons are known to have a rapid rate of chromosomal evolution among the hominoids, mainly involving large-scale rearrangements and rapid karyotypic divergence (Muller et al 2003;Carbone et al 2006;Roberto et al 2007). In contrast to human and great ape segmental duplications, where ;70% of all largescale evolutionary rearrangements map to regions of segmental duplication (Kehrer-Sawatzki and Cooper 2008), initial studies of the gibbon reported that only 46% of gibbon breakpoints mapped to sites of segmental duplication in the human lineage (Carbone et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The average breakpoint resolutions of these two studies were ;80 kbp and 200 kbp, respectively (Carbone et al 2006;Roberto et al 2007). At this level of resolution, molecular mechanisms causing synteny breaks were not clear; however, segmental duplications were estimated to be associated with 46% of the rearrangements (Carbone et al 2006).…”
mentioning
confidence: 93%
See 3 more Smart Citations